2018
DOI: 10.1021/acs.jpcb.8b10145
|View full text |Cite
|
Sign up to set email alerts
|

27Al Pulsed Field Gradient, Diffusion–NMR Spectroscopy of Solvation Dynamics and Ion Pairing in Alkaline Aluminate Solutions

Abstract: Pulsed field gradient nuclear magnetic resonance (PFG-NMR) measurements were successfully applied to the 27Al (I = 5/2) nucleus in concentrated electrolytes to investigate the diffusion of aluminate ions [Al­(OH)4 –] in simulant high-level nuclear waste (3 M NaOH) between 25 and 85 °C. The temperature-dependent diffusion coefficients obtained from 1H, 23Na, and 27Al PFG-NMR were well fit by a Vogel–Fulcher–Tammann model and a power law equation. Comparison of 27Al diffusion coefficients of 0.1 M Al­(OH)4 – in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Diffusion ordered nuclear magnetic resonance (DOSY NMR) constitutes a very useful technique for complex analysis of self-assembly in disperse systems (e.g., surfactants [26], block copolymers [27,28]), as well as other dynamic systems (e.g., micro-and nanoemulsions [29] and aggregating complex ions [30]). The mentioned approach has been employed in the determination of critical micelle/critical aggregation concentrations [31] and hydrodynamic diameters of unimers and macromolecular complexes via the Stokes-Einstein equation [27].…”
Section: Nmr Diffusometry Studies Upon Self-organization Of Hydrophobically Functionalized Poly(acrylic Acid)mentioning
confidence: 99%
See 1 more Smart Citation
“…Diffusion ordered nuclear magnetic resonance (DOSY NMR) constitutes a very useful technique for complex analysis of self-assembly in disperse systems (e.g., surfactants [26], block copolymers [27,28]), as well as other dynamic systems (e.g., micro-and nanoemulsions [29] and aggregating complex ions [30]). The mentioned approach has been employed in the determination of critical micelle/critical aggregation concentrations [31] and hydrodynamic diameters of unimers and macromolecular complexes via the Stokes-Einstein equation [27].…”
Section: Nmr Diffusometry Studies Upon Self-organization Of Hydrophobically Functionalized Poly(acrylic Acid)mentioning
confidence: 99%
“…The fitted functions and data points (for the marked functions from Table 1) are presented in Figure 2. aggregating complex ions [30]). The mentioned approach has been employed in the determination of critical micelle/critical aggregation concentrations [31] and hydrodynamic diameters of unimers and macromolecular complexes via the Stokes-Einstein equation [27].…”
Section: Nmr Diffusometry Studies Upon Self-organization Of Hydrophobically Functionalized Poly(acrylic Acid)mentioning
confidence: 99%
“…For example, understanding how the dominant tetrahedrallycoordinated aluminate anion, Al(OH) 4 -, transforms to octahedral aluminum (Al) during the precipitation of gibbsite, α-Al(OH) 3 , is key to the efficiency of the Bayer process by which alumina, Al 2 O 3 , is extracted from bauxite ore. [1][2][3] Despite the fact that the Bayer process was invented over 120 years ago and is still used to produce nearly all of the world's Al 2 O 3 supply as an intermediate step to Al production, the mechanism and kinetics of α-Al(OH) 3 precipitation have not been comprehensively described. [4][5][6][7][8][9] Both synthetic and industrial Bayer liquors have a propensity to become supersaturated, 10,11 presenting a considerable engineering challenge as α-Al(OH) 3 precipitation suffers from slow kinetics and yields are poor even in the presence of seed crystals. 12,13 Limited mechanistic understanding of how small Al clusters of low nuclearity condense into extended sheet structures of Al octahedra in α-Al(OH) 3 , or boehmite, AlO(OH) also directly hampers the processing of ca.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Despite these advantages this approach has received limited attention to date. 5,25 Here, we explore the principle aluminate species present in caustic aluminate solutions by precipitating solid phases from supersaturated KOH, RbOH, and CsOH solutions and employing multi-modal solid phase characterization to resolve the bonding environment around the Al atom. For the first time, the monomeric cesium aluminate hydroxy hydrate salt, CsAl(OH) 4 •2H 2 O, was isolated from solution, and shown by single crystal X-ray diffraction (XRD) to exhibit unusually short ….O…O interactions between the terminal hydroxide O atoms and that of the water molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of 27 Al PFGSTE NMR for analysis of ϵ-Al 13 is unique to this study, 27 Al PFGSTE NMR has been used in other instances to measure the diffusion of relatively small ions in either molten salts or concentrated electrolyte solutions. [36][37][38] Here, it is demonstrated that the symmetry and low quadrupolar coupling properties of the tetrahedral core in the ϵ-Al 13 clusters allow its diffusion to be measured with modern gradient coils. The diffusion coefficient measured by 27 Al PFGSTE NMR diffusometry of ϵ-Al 13 is then used to estimate the hydrodynamic radius of the Keggin cluster by applying Equation 1.…”
Section: Introductionmentioning
confidence: 99%